If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(7 + 5x) = 0 (7 * 5x + 5x * 5x) = 0 (35x + 25x2) = 0 Solving 35x + 25x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '5x'. 5x(7 + 5x) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(7 + 5x)' equal to zero and attempt to solve: Simplifying 7 + 5x = 0 Solving 7 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 5x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 5x = 0 + -7 5x = 0 + -7 Combine like terms: 0 + -7 = -7 5x = -7 Divide each side by '5'. x = -1.4 Simplifying x = -1.4Solution
x = {0, -1.4}
| -15=-5x-5(x-17) | | 2s^2+s+3=0 | | 2(x-3)-x=-2 | | 115=2x-3(-6x-5) | | -13x=40 | | X/(3x-5)=(1/2) | | 8n+2(n+5)= | | 4x+3(2x+11)=123 | | cos(3x)+2cos(2x)-5cos(x)-6=0 | | x*4+3=4-9 | | 5(1-x)+8x=3(x+2) | | abs(4-5x)=64 | | 2cos(7x)+1=2 | | P-6=88 | | (4x*10)/x | | 12x/48 | | -5+15x=13x+11 | | -3x+6(2x+11)=156 | | 5x-8=2x | | X-4/4=11 | | 5x=13+5x | | 1/2=14-x/6 | | 7m-4=2(5m-2)+6 | | 6x-6(-2x+4)=156 | | 2(x+5)+4(2x-1)=8x+12 | | 14x-10+6x-10=180 | | 10(h+1)-4=13 | | 3x/(3x-5)=(1/2) | | -4(t-3)=32 | | 0.3+0.2x=0.4+0.05 | | -3(x+5)=60 | | 3x+19=93 |